IMPLEMENTATION OF VALUE-BASED EDUCATION FOR YOUTH EMPOWERMENT IN DELTA STATE SECONDARY SCHOOLS: AN EMPIRICAL EXAMINATION OF CHALLENGES AND IMPROVEMENT STRATEGIES (Journal of Association of Educational Management and Policy Practitioners, 2026)
This study examined the implementation of value-based education for youth empowerment in Delta State secondary schools, with focus on the challenges and improvement strategies. The employed a descriptive survey design, which is suitable for collecting data on the current state of value-based education implementation, the challenges faced, and potential improvement strategies in Delta State secondary schools. As such three research questions guided the study. The population for this study consisted of about 12, 943 educatorscomprising all secondary school principals (488), vice principals (976) and (11,479) teachers involved in value-based education programmes across the public secondary schools in Delta State. A stratified random sampling technique was used to select 375 respondents to ensure representation from various staff (that is; principals, vice principals and teachers) in different geographical zones within Delta State.Data were collected using a 4-point scale self-structured questionnaire titled: “Implementation of Value-Based Education for Youth Empowerment: Challenges and Improvement Strategies Questionnaire (IVBEYECISQ)”. The questionnaire was face and content validated by three experts from the Faculty of Education, Chukwuemeka Odimegwu Ojukwu University, Igbariam, Anambra State. A pilot test was conducted on 30 educators in a neighboring State, that is, Edo State, with similar characteristics to Delta State. The reliability of the instrument was assessed using Cronbach’s alpha coefficient, with an acceptable reliability level set at 0.67, 0.81 and 0.70 for the three clusters respectively; which were later summed up and divided to yield an overall reliability value of 0.73, indicating a high level of internal consistency. Data collected were quantitatively analyzed using descriptive statistics such as frequencies, means statistics rated at 2.50 and standard deviation to answer the research questions. Findings of the study indicated among others thatthe extent of implementation of value-based education programmes for youth empowerment in secondary schools in Delta State was to a low extent, also indicating a moderate level of implementation. Hence, the extent of implementation of value-based themes such as honesty, discipline, responsibility, leadership and civic duties into curricular subjects like Civic Education, Social Studies, and Christian/Moral Educationfor youth empowerment was to a low extent. The study recommended among others that the Delta State Government in collaboration with the Post Primary Education Board (PPEB) and school management should ensure effective implementation of value-based education programmes for youth empowerment in secondary schools in Delta State to a high extent through effective inclusion and integration of value-based education themes and contents in the curriculum, adequate funding and establishment of VBE programmes in schools through clubs, societies and leadership training programmes.